Information and Communication Technology (ICT) and local governance : a case study of Perbadanan Putrajaya / Ahmad Saiful Azlin Puteh Salin - Puteh Salin, Ahmad Saiful Azlin (2006)
Rapid advancements in the field of information and communication technology (ICT) have significant effects on organizations to fulfill their objectives. However, the extent of ICT adoption by the local authorities in Malaysia to enhance their local governance is still under research. This study was carried out with the objectives to analyse the initiatives of Perbadanan Putrajaya, a local authority responsible of managing Putrajaya in incorporating ICT in its local governance. It also explored the trends in local governance and find out how ICT affected these trends. Furthermore, it's determined the factors that underpinned Perbadanan Putrajaya to incorporate ICT in its governance. An interview was conducted with the Deputy Director of the Information System Division and observations were also made with regards to the community portal of Perbadanan Putrajaya, MyPutrajaya.net. The findings suggested that the implementation of the ICT Master Plan and the community portal were the major initiatives taken by Perbadanan Putrajaya in incorporating ICT in its local governance. Moreover, all the six local governance trends examined namely integrated, transparent, developmental, strategic, networking and promotional did exist and ICT had enhanced them further. Finally, it was concluded that policy, economy and technology are the important factors that underpinned the capability of Perbadanan Putrajaya to incorporate ICT in its local governance.